2018
DOI: 10.17986/blm.2018345599
|View full text |Cite
|
Sign up to set email alerts
|

Çocuklarda Suç Tekrarını Yordayan Risk Faktörleri

Abstract: Amaç: Suça sürüklenen çocukların tekrar suça sürüklenmesine ilişkin risk faktörlerinin belirlenmesi, tekrarlayan suça sürüklenmelerin önlenebilmesi için önem arz etmektedir. Mevcut çalışmanın amacı suça sürüklenen çocukların tekrar suça sürüklenmesini yor- dayan değişkenlerin belirlenmesidir. Bu bağlamda, tek bir defa suça sürüklenen çocuklar ile üç ve daha fazla suça sürüklenen çocukların karşılaştırılması yoluyla çocukların birçok kere suça sürüklenmesini yordayan faktörlerin ortaya çıkarılması hedeflenmekte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In a study conducted by Erbay and Gülüm (2018), it was found that the risk factors of children prosecuted with criminal charges fall into two main groups. In the first group, there are factors that can be evaluated in the category of individual reasons such as running away from home, self-harm, drug use, dropping out of school.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Erbay and Gülüm (2018), it was found that the risk factors of children prosecuted with criminal charges fall into two main groups. In the first group, there are factors that can be evaluated in the category of individual reasons such as running away from home, self-harm, drug use, dropping out of school.…”
Section: Introductionmentioning
confidence: 99%
“…One observes that overall, the literature focuses on adolescence as a period associated with children who become involved in crime ( Brugman and Aleva, 2004 ; Güçlü and Akbaş, 2019 , p. 323; Ögel, 2014 ) or display early-onset behavior problems ( Shader, 2001 ; Fergusson et al, 2005 ). In addition, scholars have researched how the following relating to juvenile crime or victimization: psychiatric disorders ( Pratt et al, 2002 ; Moore et al, 2013 ), family structure ( Köknel, 2001 ; Thompson and Bynum, 2016 ), parenting characteristics ( Loeber, 1990 ; Wright and Cullen, 2001 ), substance use ( Assink et al, 2015 ; Belenko et al, 2017 ), social problems ( Farrington and Welsh, 2008 ; Neto, 2009 ; Gönültaş and Kelebek, 2017 ), friendship relationships ( Gül and Güneş, 2009 ; Susanu, 2019 ; Walters, 2019 ), and educational experiences ( Maguin and Loeber, 1996 ; Cullen et al, 2008 ; Erbay and Gülüm, 2018 ).…”
Section: Introductionmentioning
confidence: 99%